2017
DOI: 10.2337/db17-0441
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Differences in Fructosamine-3-Kinase Activity May Be Associated With the Glycation Gap in Human Diabetes

Abstract: The phenomenon of a discrepancy between glycated hemoglobin levels and other indicators of average glycemia may be due to many factors but can be measured as the glycation gap (GGap). This GGap is associated with differences in complications in patients with diabetes and may possibly be explained by dissimilarities in deglycation in turn leading to altered production of advanced glycation end products (AGEs). We hypothesized that variations in the level of the deglycating enzyme fructosamine-3-kinase (FN3K) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 32 publications
(40 reference statements)
0
15
0
Order By: Relevance
“…The latter are unstable and spontaneously decompose into inorganic phosphate and 3-deoxyglucosone, regenerating the unglycated amine (Gugliucci, 2005). The presence of proteins related to fructosamine 3-kinase in many prokaryotic and eukaryotic genomes implies that this ‘deglycation’ process is not restricted to erythrocytes nor to just mammals (Collard et al, 2004; Dunmore et al, 2018; Van Schaftingen et al, 2007; Szwergold et al, 2011). …”
Section: The Maillard Reaction: Initiators Propagators and Chemistrymentioning
confidence: 99%
“…The latter are unstable and spontaneously decompose into inorganic phosphate and 3-deoxyglucosone, regenerating the unglycated amine (Gugliucci, 2005). The presence of proteins related to fructosamine 3-kinase in many prokaryotic and eukaryotic genomes implies that this ‘deglycation’ process is not restricted to erythrocytes nor to just mammals (Collard et al, 2004; Dunmore et al, 2018; Van Schaftingen et al, 2007; Szwergold et al, 2011). …”
Section: The Maillard Reaction: Initiators Propagators and Chemistrymentioning
confidence: 99%
“…FN3K is highly expressed in erythrocytes with a documented role in HbA1c variation independent of glucose levels [16]. It was reported that FN3K enzyme activity and protein levels were both significantly higher in patients with a negative glycation gap (lower HbA1c levels than would be expected from average glycemia) [16]. The HGI calculated using MBG levels was strongly correlated with the HGI calculated using only pre-breakfast glucose (r=0.867) or FBG (r=0.687) levels.…”
Section: Discussionmentioning
confidence: 99%
“…If an individual has a measured HbA1c that is higher than expected from MBG levels (i.e., a high HGI), higher measured HbA1c levels than would be expected from MBG levels is likely to continue during repeated comparisons over time. Such individuals likely have a relatively long red blood cell (RBC) life span (i.e., a slow RBC turnover rate), a relatively high RBC glycation rate, or a variation in another yet undefined biological or genetic factor [15,16]. Genetic variations could influence HbA1c levels through nonglycemic pathways and contribute to HbA1c/glycemia discordance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49 The enzyme fructosamine-3-kinase is highly expressed in erythrocytes and promotes deglycation of proteins and is one of the mechanisms contributing to changes in HbA1c not related to glucose levels. 51 Several reports have shown that Black individuals have systematically higher HbA1c levels than Whites. Furthermore, HbA1c has been associated with the imprecise classification of T2DM in the Black population than in Whites.…”
Section: Hba1cmentioning
confidence: 99%